(untitled) (Global Journal of Science Frontier Research, 2016)
Plants have been one of the important sources of medicines since the beginning of human civilization. There is a growing demand for plant based medicines, health products, pharmaceuticals, food supplements and cosmetics. Murraya koenigii commonly called curry leaf tree is a multipurpose tree and is a source one of the medicinal products. Different parts of M. koenigii are used in folkloric medicine for the treatment of various diseases. It is proved to possess significant wound healing capacity and shows antioxidant activity with high degree of radical-scavenging properties. This article intends to provide an overview of the chemical constituents present in the crude leaf extracts of M. koenigii with special emphasis on their pharmacological actions. Qualitative phytochemical screening was carried out using the crude leaf extracts in three different solvents such as water, alcohol and chloroform. Phytochemical analysis of the extracts revealed the presence of glycosides, alkaloids, oils, sapponins and flavanoids.